Antibiotics in the Treatment of Periodontitis: A Systematic Review of the Literature - Chaima Hammami; Wafa Nasri (Hindawi Limited, 2021)
Introduction. Systemic antibiotics present one of the alternative adjunctive therapies in nonsurgical periodontal treatment (NSPT). Different protocols have been proposed, but their indication and effectiveness are still controversial. The aim of this study is to assess the effectiveness of the addition of antibiotics after nonsurgical debridement during initial therapy and compare different antimicrobial prescription protocols. Materials and Methods. An electronic search was performed through MEDLINE and EBSCOhost databases using the appropriate MeSH words. The target studies have to be published during the last five years. Data from the selected studies were extracted and analyzed. Study selection was done based on inclusion and exclusion criteria. Results. Seven randomized clinical trials were included in our review. Their data were extracted using a grid established for this purpose. Collectively, different protocols have been proposed and almost all of them yield superior clinical and microbiological results compared to the placebo group. Conclusion. The overall findings of this review show a positive effect of the use of antibiotics as an adjunctive to NSPT, regardless of the antimicrobial agents used in our included studies. Sites with PD > 6 mm may benefit most from the adjunctive use of antibiotics in NSPT. This trial is registered with Clinicaltrials.gov identifiers: NCT02829983 (Bechara Andere et al., 2016); NCT02839421 (Ardila et al., 2020); NCT02735395 (Borges et al., 2017); NCT02359721 (Suryaprasanna et al., 2018); and NCT01318928 (Hans, 2015).